2023
DOI: 10.1161/circoutcomes.122.009348
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Weight Regain Following Behavioral Weight Management Programs on Cardiometabolic Disease Incidence and Risk: Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Behavioral weight management programs (BWMPs) enhance weight loss in the short term, but longer term cardiometabolic effects are uncertain as weight is commonly regained. We assessed the impact of weight regain after BWMPs on cardiovascular risk factors, diabetes, and cardiovascular disease. METHODS: Trial registries, 11 databases, and forward-citation searching (latest search, December 19) were used to identify articles published in English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 149 publications
1
7
0
Order By: Relevance
“…Although 5% weight loss is typically considered clinically meaningful, some evidence has suggested that weight loss of less than 5% may be clinically important . Providing participants with cash that they could retain if they met study goals may have facilitated enrollment of participants with lower incomes, in contrast to deposit contract financial incentives where participants risk losing their own money .…”
Section: Discussionmentioning
confidence: 99%
“…Although 5% weight loss is typically considered clinically meaningful, some evidence has suggested that weight loss of less than 5% may be clinically important . Providing participants with cash that they could retain if they met study goals may have facilitated enrollment of participants with lower incomes, in contrast to deposit contract financial incentives where participants risk losing their own money .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Quality and Outcomes, Hartmann-Boyce et al 7 examined the extensive body of literature on weight regain following BWMPs to characterize the impact of initial weight loss and then weight regain on cardiometabolic risk factors (blood pressure, glycemic control, and cholesterol) and on incident cardiovascular disease and T2DM. Among over 17 000 studies, they found only 124 randomized control trials which reported on ≥1 cardiometabolic outcome with at least 12 months of follow-up.…”
Section: See Article By Hartmann-boyce Et Almentioning
confidence: 99%
“…In this study, weight loss following BWMP and subsequent regain are associated with favorable, although modest changes in cardiometabolic risk factors, yet, long-term data are insufficient in characterizing the association between weight changes and cardiovascular death, myocardial infarction, or stroke. 7 Understanding long-term clinical outcomes is important because BWMPs are often resource intensive, and the emerging pharmacologic therapies are expensive. On a population level, it is critical to fully evaluate the economic impact of these weight loss strategies, especially in a condition that leads to high health care costs.…”
Section: See Article By Hartmann-boyce Et Almentioning
confidence: 99%
“…The obesity paradox refers to the seemingly counterintuitive notion that body mass index (BMI) is not a consistent cardiovascular risk factor in overweight and obese individuals ( 7 , 8 ), and questions the cardiovascular health benefits of weight loss in the long term ( 9 11 ). Body weight variability has been examined as an additional risk factor to explain the controversial findings on the effect of weight loss on CVD and mortality ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%